A219 HEPATITIS C IN NOVA SCOTIA PATIENTD WITH HEREDITARY BLEEDING DISORDERS: AUDIT FOR IDENTIFICATION OF PATIENTS FOR POTENTIAL TREATMENT WITH DIRECT ACTING ANTIVIRAL AGENTS. (1st March 2018) - Alahmadi, A; Mishra, S; Hirsch, G; carla, B; Robinson, K; Peltekian, K M
Abstract: Background: Individuals with hereditary bleeding disorders (HBD) represent a unique population who were exposed to hepatitis C virus (HCV) through blood products prior to 1990. The Krever Commission in 1997 described the flawed organization of blood product delivery in Canada and recommended the federal/provincial governments identify and treat these patients. Aims: Our primary goal was identifying all HBD patients with ongoing HCV viremia who would be candidates for treatment with direct acting antiviral agents. Secondary goal was to describe the burden of HCV in our cohort of HBD patients. Methods: We retrospectively audited the charts of all patients seen at the Adult Hereditary Bleeding Disorder Clinic at the Queen Elizabeth II Health Sciences Centre (QEII-HSC) in Halifax, Nova Scotia, Canada from 1997–1999 who were infected with Hepatitis C. We recorded current survival status, sustained virologic response (SVR), hepatic decompensation, and need for transplantation. Thereafter the pre-existing hepatology medical records was used to determine how many patients were referred for transplantation their status up to the summer of 2015. Results: A total of 40 HCV(+) patients, 29 males (72.5%) and 11 females (27.5%) were identified with 1 lost for follow up (2.5%). HCV-PCR was positive in 29 (80.6%). Only 15 (51.7%) were treated previously for HCV with sustained viral response in 10 (66.67%) – the majority with interferon-based therapies. Hepatic decompensation occurred in 7 patients (18%), HCC in 2 (5%), 2 underwent transplantation (5%) and 8 patients were deceased (20.5%). Conclusions: Our chart audit resulted in identification of 11 HCV infected patients who are still alive from the original cohort of 40 patients who may be candidates for therapy with interferon-free direct acting antiviral agents. Funding Agencies: None